Layout optimization of multi-material continuum structures with the isolines topology design method - Querin, Osvaldo M.; Victoria, Mariano; Díaz, Concepción; Martí, Pascual (Engineering optimization, 2015)
A heterogeneous or multi-material object is one made from different materials which are distributed continuously or discontinuously. Its properties can be adjusted by controlling the material composition, microstructure and geometry of the object. The development of manufacturing technologies such as rapid prototyping can eliminate the high cost of tooling and offers the possibility to make multi-material structures. However, designing such technologies is not a trivial task and requires the development or modifications of optimization algorithms to take into consideration the different aspects of these problems. This article presents an enhancement to the isolines topology design (ITD) algorithm that allows it to produce multi-material designs. Four examples of the topology design of two-dimensional continuum structures are presented to demonstrate that the ITD algorithm is an efficient and reliable method to achieve the layout optimization of multi-material continuum structures.